A Modified Administrative Internship: Can It Meet the Objectives of a Traditional Internship for Preparing Future Leaders? - Briscoe, Patricia (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2026)
Administrative internships providing field-based experiences are identified as an effective practice in school leadership preparation programs. However, including internships of 15 weeks with full-time on-the-job requirements is problematic in programs where students primarily work full-time. This study investigated the capacity of a modified internship approach—field-based activities and fewer hours—to achieve similar outcomes as a traditional internship. The longitudinal qualitative study involved five cohorts (n = 60) of graduate students in a Master of Educational Leadership program in Canada over five years (2019-2023). Participants completed a qualitative survey after their required internship course, and the data were analyzed using a conventional and summative qualitative content analysis approach. The findings determined that participants overwhelmingly agreed that the modified administrative internship structure effectively provided authentic experiences about the reality of school leadership roles and responsibilities and prepared them better for the role. The consistent findings spanning over five years support the validity of the modified approach, aligning with traditional internships’ goals. Leadership preparatory programs seeking to enhance the preparation of future school leaders may benefit from adopting a similar field-based course structure as the modified internship approach.